Perubahan Mata Pencaharian Masyarakat Nelayan di Kelurahan Tanjung Penyembal kecamatan sungai sembilan kota dumai - Muhammad Isnaini; Firman Nugroho; Viktor Amrifo (Berkala Perikanan Terubuk, 2016)
This research was conducted in Tanjung Penyembal Sungai Sembilan Kota Dumai in February-March 2016. The purposes of this study were (1) To identify the types of new jobs that are run by fishermen, (2) To analyze the factors that cause changes community work fishermen in Tanjung Penyembal, (3) to compare the working time of fishermen with new work undertaken by the fishing and compare household income of fishermen with household society has changed the work of fishermen, (4) to identify the impact of changes in employment which is carried out by fishermen. This study used survey method with qualitative-quantitative approach. The method to determine the respondents in this study is a census method. The results showed that (1) the new types of work fishermen are farmers, traders, farm labor, factory labor, and breeders. (2) The internal factors that cause changes in the work that is catch, income, age, knowledge and skills, and equipment fisherman. While external factors, namely the environmental conditions , government attention, innovation in other livelihood and employment risk. (3) Based on the outpouring of working hours, fishing is a job that has outpouring second longest working hours after the merchants. Meanwhile, based on revenue, the fishing was ranked fourth after traders, farmers, and ranchers. (4) The Positive Impact of occupation’s changes in fishing communities that Increased welfare of the community; Widespread community interaction region; The emergence of community motivation to improve education. While the negative impact is the reduced production of fresh fish in Tanjung Penyembal.